2019
DOI: 10.4103/njs.njs_7_18
|View full text |Cite
|
Sign up to set email alerts
|

The duration of intra-abdominal hypertension and increased serum lactate level are important prognostic markers in critically ill surgical patient's outcome: A prospective, observational study

Abstract: Aim: The present study analyzed the clinical significance of duration of intra-abdominal hypertension (IAH) associated with increased serum lactate in critically ill patients with severe sepsis. Materials and Methods: Our study was an observational, prospective study carried out in the Surgical Intensive Care Unit (ICU) at J.L.N Medical College, Ajmer, Rajasthan, India. In our study, we included a total of 100 patients and intra-abdominal pressure (IAP) was measured thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…22% of our patients came with blunt trauma of the abdomen. Studies conducted showed a similar distribution of trauma patients [7,8]. In our study, patients with ascites (3%), burn (1%), and gut gangrene (2%) constituted a small percentage.…”
Section: Dutta Et Alsupporting
confidence: 73%
See 1 more Smart Citation
“…22% of our patients came with blunt trauma of the abdomen. Studies conducted showed a similar distribution of trauma patients [7,8]. In our study, patients with ascites (3%), burn (1%), and gut gangrene (2%) constituted a small percentage.…”
Section: Dutta Et Alsupporting
confidence: 73%
“…This mean duration in our non-survivor group is 3.77±1.92 days and in the survivor group are 1.94±1.55 days. Gupta et al [8] found in their study that the mean duration of IAH in the survivor group is 2.85 days and that in the non-survivor group is 8.38 days.…”
Section: Dutta Et Almentioning
confidence: 89%
“…Serum lactate levels are a commonly raised in burn patients, and causes are multifactorial. Raised lactate is used as a surrogate marker of ischemia and hypoperfusion and has been shown to increase in established IAH 29 . Therefore, intra-abdominal pathology should always be considered when searching for causes of raised lactate (>2 mmol/L), and the intra-abdominal pressure should be checked to exclude this as a cause.…”
Section: Resultsmentioning
confidence: 99%
“…Хірургічне лікування післяопераційних вентральних гриж (ПВГ) гігантських розмірів асоціюється з виникненням інтраабдомінальної гіпертензії (ІАГ) у післяопераційному періоді. Це ускладнення обумовлене переміщенням вмісту грижового мішка, зокрема ділянок кишківника та великого чепця в черевну порожнину та закриттям великого дефекту черевної стінки, що створює передумови для інтраабдомінальної гіпертензії [1,2]. Виникнення інтраабдомінальної гіперетензії ІІІ та IV ступенів, зокрема з внутрішньочеревним тиском (ВЧТ) більше 20 мм.…”
unclassified